Utopian variations: utopia in literature, film, and popular culture - Seeger, Sean (Ralahine utopian studies, 2025)
"Utopian Variations is a comparative critical study of a variety of kinds of utopia and utopian discourse. Rather than focusing on more familiar forms of utopia, the book considers utopia in relation to a range of topics that have received less attention within utopian studies, including literary modernism, postsecularism, transhumanism, antihumanism, xenofeminism, the Covid-19 pandemic, recent speculation about postcapitalism, and utopianism since the 2007-8 financial crisis. The book also makes an entirely original argument for a re-evaluation of the concept of the utopian blueprint that breaks with academic orthodoxy in this area. As well as drawing on literature, film, and popular culture, there is extensive engagement with social theory, cultural theory, and queer theory, resulting in a rich, wide-ranging study"-- Provided by publisher